Exploring Stressors: Impact on Cellular Organelles and Implications for Cellular Functions - Zoofa Zayani; Arash Matinahmadi; Alireza Tavakolpournegari; Seyed Hesamoddin Bidooki (Stresses, 2025)
Cellular stressors have been demonstrated to exert a substantial influence on the functionality of organelles, thereby impacting cellular homeostasis and contributing to the development of disease pathogenesis. This review aims to examine the impact of diverse stressors, including environmental, chemical, biological, and physical factors, on critical organelles such as the cell membrane, mitochondria, endoplasmic reticulum, Golgi apparatus, lysosomes, and membrane-less organelles. The intricate molecular mechanisms underlying cellular stress responses, encompassing oxidative stress, protein misfolding, and metabolic reprogramming, have the capacity to elicit adaptive responses or culminate in pathological conditions. The interplay between these stressors and organelle dysfunction has been implicated in a myriad of diseases, including neurodegenerative disorders, cancer, metabolic disorders, and immune-related pathologies. A comprehensive understanding of the mechanisms by which organelles respond to stress can offer valuable insights into the development of therapeutic strategies aimed at mitigating cellular damage.